زيد بن حارثة رضي الله عنه : دراسة تاريخية في سيرته - العباسى، عمر أمجد صالح (جامعة الموصل - كلية الآداب, 2012)
The first companions biography and life represented a model and a sample of human completion in obeying Allah, Where history did not know men like them characterized by justice and highness. They sacrificed themselves with high encouragement for this life, and one of these companions was Zaid Ibn Haritha, the martyr prince in Mu'tta Raid, the master of Al-Mawali, the first Muslim, the Prophet's beloved, and Allah did not name anyone with his name accept Zaid. The man who was short, brown, snub-nosed, the one who found for himself a place in the Prophet's heart (Peace and blessings be upon him), Allah said. (The most honorable of you will Allah is that (believ er) who has Al-Taqwa). Also the Prophet said: (There is on difference between Arabs and non-Arabs accept with fear of God), where in this brighter religion Bilal, Suliaib, Ammar. Khabab, Usama and Zaid are near to Allah in the highest Paradise.
Keywords: الدراسات الإسلامية -- زيد بن حارثة بن شراحيل الكلبي ، ت 8 هـ -- السمات الشخصية -- محمد صلى الله عليه وسلم -- التراجم -- تفسير القرآن -- المؤلفات -- العصر الجاهلي -- السيرة النبوية